Critical evaluation of ceftolozane–tazobactam for complicated urinary tract and intra-abdominal infections - Giancola SE; Mahoney MV; Bias TE; Hirsch EB (Dove Medical Press, 2016)
Stephanie E Giancola,1 Monica V Mahoney,2 Tiffany E Bias,3,4 Elizabeth B Hirsch2,51Department of Pharmacy, St Mary’s Medical Center, Huntington, WV, 2Beth Israel Deaconess Medical Center, Boston, MA, 3Hahnemann University Hospital, 4Drexel University College of Medicine, Philadelphia, PA, 5Department of Pharmacy and Health Systems Sciences, Northeastern University, Boston, MA, USAAbstract: The rise in resistant Gram-negative pathogens continues to challenge clinicians treating infections. These resistant infections have inspired the development of new antimicrobial agents, including ceftolozane–tazobactam, a novel β-lactam/β-lactamase inhibitor combination approved by the US Food and Drug Administration for the treatment of complicated urinary tract infections (cUTIs) and complicated intra-abdominal infections (cIAIs) in combination with metronidazole. Ceftolozane exhibits bactericidal activity by inhibiting penicillin-binding proteins (PBPs), with high affinity for PBP1b, PBP1c, and PBP3. The addition of tazobactam protects ceftolozane from hydrolysis by irreversibly binding to some β-lactamase enzymes. Ceftolozane–tazobactam is active against a wide range of Gram-negative pathogens, including extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae and multidrug-resistant (MDR) Pseudomonas aeruginosa, several streptococcal species, and Bacteroides fragilis. When anaerobic coverage is needed, it should be used in combination with metronidazole. Ceftolozane demonstrates linear pharmacokinetics, low protein binding, and minimal accumulation with repeated dosing. The major pharmacokinetic/pharmacodynamic index for ceftolozane is the percentage of the dosing interval in which the plasma free drug concentration remains higher than the minimum inhibitory concentration (%T>MIC). Phase III clinical trials for the treatment of cUTIs and cIAIs have been completed, showing that it is an effective and safe alternative for the treatment of these infections. The approved dose for cUTIs and cIAIs is 1.5 g (1 g ceftolozane and 500 mg tazobactam) infused over 1 hour every 8 hours. A higher 3 g dose is currently in Phase III trials for the treatment of ventilated nosocomial pneumonia. Dosage adjustments are necessary for patients with moderate-to-severe renal impairment. Current data suggest that ceftolozane–tazobactam is a promising carbapenem-sparing alternative agent for the treatment of cUTIs and cIAIs, including those caused by ESBL-producing Enterobacteriaceae and MDR P. aeruginosa.Keywords: multidrug-resistant, UTI, resistance, β-lactamase